The Effect of Financial Distress on Capital Structure in Indonesia Banking Sector - Deliana, Deliana; Nugroho, Vina (Proceedings of the International Conference on Entrepreneurship (IConEnt), 2023)
Banking industry is believed as a vanguard of a country’s economy. If a bank experiences financial distress, not only that bank will face financial difficulties, but also have a systemic impact on all customers of that bank. So, capital structure of banking industry is a crucial thing. Capital structure in this study is proxied by Leverage Ratio. All of companies need leverage, but if leverage seems too high, it will have bad consequences for the company itself. Then, Banks, which are industry that really needs high liquidity also need leverage. Especially, when financial distress occurs, whether banks need to increase the proportion of their debt or not in order to survive. This research uses 23 commercial banks in Indonesia with quarterly panel data from 2012 to 2022. Results of this study state that Financial Distress can have a significant positive effect on increasing the Leverage Ratio of banks in Indonesia.